Competências requeridas pelos gerentes de enfermagem hospitalar - Finger, Adriane (2012)
After the base and the structure formed on a monastic regime of devotion and charity, nursing has changed in profile, from activity, regulated and respected profession. Through new assignments given to nurses, it became necessary that it receive a better training their functions in modernity, which also include care management of the health unit (U.S.) where he works. From this observation defined the research problem that guided this study: What are the skills of knowledge, skills and attitudes considered of extreme importance to nursing managers?, Whose objectives are to: - Identify the level of importance of skills knowledge, skills and attitudes, according to the perception of nursing managers; - To characterize the population of nursing managers of the research institution; - Identify the skills considered extremely important by the respondents; - Talking about the skills considered extremely important by respondents. To achieve the objectives has been carried out field research, exploratory, descriptive and quantitative approach, which had 25 managers as subjects of a U.S. teaching hospital, the large city of Santa Maria-RS. A survey conducted in 2011, used a research tool in two parts: a) sociodemographic information; b) 51 items for the election of skills related skills (20 items), knowledge (16) and attitudes (15) considered extremely important for nurse managers. The result showed that among the skills considered extremely important by the nurses are: a) Knowledge: Know the health policy (62.50%); know the mission and goals of the health institution (75.00%); Knowing services developed in the U.S. (79.16%), knowledge of rules and procedures (70.83%); Knowledge of quality of service (72.73%), b) skill: Being able to communicate adequately with staff and users (95.83%); Being ethical with staff, superiors, and users (91.67%); Being able to promote and maintain relationships with staff and users (87.50%); To identify problems (82 , 61%), c) attitudes: Be fair to your team and users (70.83%); Be open to change (70.83%); have involvement with work, with staff and community (70.83% ) What favors teamwork (70.83%); Who knows accept criticism (70.83%). From the results it appears that the respondents consider very important for the unit manager skills that added to the profile will comprise an individual who has knowledge of public policies, standards, mission and objectives and assessing the quality of their work, able to communicate with others appropriately, with an ethical procedure, companionship and attention to problems, flexible, engaging, and participatory, with humility toward criticism. It is noticed that all these skills are combined in one person make up the ideal professional, morally and technically qualified to take up his managerial position, care and citizen, with ethics, knowledge and determination. The search result leaves perceive the need for further studies to investigate whether nurse managers are putting into practice in their daily life skills they consider extremely important, so that your professional performance achieves the desired objectives by all.